Experimental study on the hydrodynamic impact of tsunami-like waves against impervious free-standing buildings. Issue 2 (3rd April 2018) - Wüthrich, Davide; Pfister, Michael; Nistor, Ioan; Schleiss, Anton J.
ABSTRACT: Tsunamis, landslide-generated waves, and dam failures are rare, but highly destructive phenomena, associated with extreme loading on infrastructure. Recent events showed that specific measures must be taken to guarantee safety of both people and the built environment. This experimental study investigates the forces and moments exerted on free-standing buildings that are induced by both surges and bores. The hydrodynamic impact was characterized by high splash, subsequently followed by a quasi-steady flow around the structure. For dry bed surges, the time history of the horizontal force was proportional to the momentum flux per unit width. For wet bed bores, an attenuation of the peak force due to the presence of an aerated front was observed and the introduction of a reduction coefficient was necessary to achieve a realistic force estimation. Additional force analysis in terms of peak time, wave height at maximum force and impulse also pointed out some key differences between forces exerted by dry bed surges and wet bed bores. The occurrence of the maximum tilting moment on the building coincided with the maximum horizontal force and an evaluation of the cantilever arm was possible. These findings provide engineers with practical information for the design of safer coastal structures.